Plant–Aphid Interactions Under Elevated CO2: Some Cues from Aphid Feeding Behavior - Sun, Yucheng; Guo, Huijuan; Ge, Feng (Frontiers in Plant Science, 2016)
Although the increasing concentration of atmospheric carbon dioxide (CO2) accelerates the accumulation of carbohydrates and increases the biomass and yield of C3 crop plants, it also reduces their nitrogen status. The consequent changes in primary and secondary metabolites affect the palatability of host plants and the feeding of herbivorous insects. Aphids are phloem feeders and are considered the only feeding guild that positively responds to elevated CO2. In this review, we consider how elevated CO2 modifies host defenses, nutrients, and water-use efficiency by altering concentrations of the phytohormones jasmonic acid, salicylic acid, ethylene, and abscisic acid. We will describe how these elevated CO2-induced changes in defenses, nutrients, and water status facilitate specific stages of aphid feeding, including penetration, phloem-feeding, and xylem absorption. We conclude that a better understanding of the effects of elevated CO2 on aphids and on aphid damage to crop plants will require research on the molecular aspects of the interaction between plant and aphid but also research on aphid interactions with their intra- and inter-specific competitors and with their natural enemies.